Ilmu Akhlaq sebagai Pengembangan Keilmuan dalam Perspektif Filsafat Ilmu - Addin Mustaqim; M. Yunus Abu Bakar (Jurnal Budi Pekerti Agama Islam, 2025)
The development of responsible knowledge requires a strong moral foundation, one of which is through the application of akhlakul karimah (noble character). Good, noble, and commendable ethics play a crucial role in creating knowledge that is not only practically beneficial but also has a positive impact on humanity and the environment. The main issue addressed in this study is how akhlakul karimah can shape the behavior of scientists in developing ethical knowledge and how it contributes to the construction of responsible science. This research employs a library research approach. The findings indicate that akhlakul karimah is essential in guiding scientists to uphold integrity, honesty, and social responsibility in research and the application of knowledge. Scientists with noble character do not only prioritize technological advancements but also consider the balance between material progress and the moral and spiritual quality of human life. Thus, akhlakul karimah plays a vital role in ensuring that scientific development remains responsible and contributes positively to humanity and environmental sustainability.